Loss of NGF-TrkA signaling from the CNS is not sufficient to induce cognitive impairments in young adult or intermediate-aged mice. - Müller, M; Triaca, V; Besusso, D; Costanzi, M; Horn, J; Koudelka, J; Geibel, M; Cestari, V; Minichiello, L (2012)
Many molecules expressed in the CNS contribute to cognitive functions either by modulating neuronal activity or by mediating neuronal trophic support and/or connectivity. An ongoing discussion is whether signaling of nerve growth factor (NGF) through its high-affinity receptor TrkA contributes to attention behavior and/or learning and memory, based on its expression in relevant regions of the CNS such as the hippocampus, cerebral cortex, amygdala and basal forebrain. Previous animal models carrying either a null allele or transgenic manipulation of Ngf or Trka have proved difficult in addressing this question. To overcome this problem, we conditionally deleted Ngf or Trka from the CNS. Our findings confirm that NGF-TrkA signaling supports survival of only a small proportion of cholinergic neurons during development; however, this signaling is not required for trophic support or connectivity of the remaining basal forebrain cholinergic neurons. Moreover, comprehensive behavioral analysis of young adult and intermediate-aged mice lacking NGF-TrkA signaling demonstrates that this signaling is dispensable for both attention behavior and various aspects of learning and memory.